Molecular characterization of six sub population Indonesian local goats based on mitochondrial DNA D-loop - Aron Batubara; R.R. Noor; A. Farajallah; B. Tiesnamurti; M. Doloksaribu (Indonesian Center for Animal Research and Development (ICARD), 2011)
Indonesian local goats were spread in some region, but there was still limited data’s known about the characteristics of its genetic diversity and origin. The Mitochondrial DNA D-loop sequences were used to study the genetic diversity and relationships of six sub population Indonesian local goats, namely, Kacang, Marica, Samosir, Jawarandu, Muara and Bengali goats. From 539 blood samples and DNA extraction collections were selected about 60 samples (10 samples each sub populations) analyzed by PCR-RFLP methods, followed sequence analyzed about 5 PCR products each sub population. The results of the sequence analyses were edited and acquired about 957 bp of nucleotides length. After the alignment analyses were found 50 polymorphic sites which divided into 19 haplotype groups of mtDNA D-loop region. The value of nucleotide diversity was 0.014 ± 0.002. Analysis of Neighbour Joining with Kimura 2 Parameter methods and bootstrap test with 1000 replication indicated that each sub population groups was significantly different between one groups to the others. The maternal lineages origin of six breeds of Indonesian local goats was included to the group of lineage B. The Lineage B was the maternal origin of the haplogroup of goats in the region of East Asia, South Asia, China, Mongolia, North and South Africa, Malaysia, Indonesia, Pakistan and India. Key words: Genetic Diversity, mtDNA D-loop, Haplotypes, Local Goats